Cyclomodulins and Hemolysis in E. coli as Potential Low-Cost Non-Invasive Biomarkers for Colorectal Cancer Screening - Mezerová, Kristýna; Starý, Lubomír; Zbořil, Pavel; Klementa, Ivo; Stašek, Martin; Špička, Petr; Skalický, Pavel; Raclavský, Vladislav (Life (Basel, Switzerland), 2021)
The frequent occurrence of E. coli positive for cyclomodulins such as colibactin (CLB), the cytotoxic necrotizing factor (CNF), and the cytolethal distending factor (CDT) in colorectal cancer (CRC) patients published so far provides the opportunity to use them as CRC screening markers. We examined the practicability and performance of a low-cost detection approach that relied on culture followed by simplified DNA extraction and PCR in E. coli isolates recovered from 130 CRC patients and 111 controls. Our results showed a statistically significant association between CRC and the presence of colibactin genes clbB and clbN, the cnf gene, and newly, the hemolytic phenotype of E. coli isolates. We also observed a significant increase in the mean number of morphologically distinct E. coli isolates per patient in the CRC cohort compared to controls, indicating that the cyclomodulin-producing E. coli strains may represent potentially preventable harmful newcomers in CRC patients. A colibactin gene assay showed the highest detection rate (45.4%), and males would benefit from the screening more than females. However, because of the high number of false positives, practical use of this marker must be explored. In our opinion, it may serve as an auxiliary marker to increase the specificity and/or sensitivity of the well-established fecal immunochemical test (FIT) in CRC screening.
Keywords: colibactin; screening; colorectal cancer; cytotoxic necrotizing factor; genotoxin